4. PNEUMATIC TEMPERATURE SENSOR FAILURE ANALYSIS P/N 767C0000-01 ON AN AIRBUS 330-300 AIRCRAFT AT PT GMF AEROASIA - Muhammad Ghani; Al Hafidz; Ego Widoro; Benny Kurniantoi; Muchammad Furqon; Kurniawan; Tia Dikatama (Jurnal TNI Angkatan Udara, 2026)
This study aims to analyze the causes of sensor failure at PT GMF AeroAsiaTbk. The methodology used was observation, interviews, and document analysis. Modernaircraft rely heavily on reliable support systems, including pneumatic systems for regulatingcabin temperature and safety. On an Airbus A330-300, a problem with the pneumatictemperature sensor was found, with corrosion on the sensor rod resulting in inaccuratetemperature readings that could impact flight safety. This study aimed to analyze the causesof sensor failure at PT GMF AeroAsia Tbk. The methodology used was observation,interviews, and document analysis. Data were analyzed using Pareto charts and Fault TreeAnalysis to identify the root cause. The results indicated that corrosion was the primarycause, exacerbated by environmental factors, weak inspection procedures, and a lack oftechnician understanding. In conclusion, the sensor failure was caused by a combination oftechnical, procedural, and human factors. This research helps develop better aircraftmaintenance strategies to improve safety.